Plasmodium vivax: functional analysis of a highlyconserved PvRBP-1 protein region. (2001)
Plasmodium vivax is one of the most prevalent malarial species around the world [1]. Two P. vivax reticulocyte binding proteins (PvRBP-1 and PvRBP-2), expressed at the apical pole of this parasite, are considered to be the binding ligands involved in the specific selection of this younger red blood cell population [2]. The adhesion of the PvRBP complex, to an unknown receptor on the target cells, does not depend on the presence of the red blood cell Duffy glycoprotein, this being strictly a receptor for the PvDBP protein.